2007
DOI: 10.1021/np070307c
|View full text |Cite
|
Sign up to set email alerts
|

Pinpointing Pseurotins from a Marine-DerivedAspergillusas Tools for Chemical Genetics Using a Synthetic Lethality Yeast Screen

Abstract: A new compound of mixed polyketide synthase-nonribosomal peptide synthetase (PKS/NRPS) origin, 11- O-methylpseurotin A ( 1), was identified from a marine-derived Aspergillus fumigatus. Bioassay-guided fractionation using a yeast halo assay with wild-type and cell cycle-related mutant strains of Saccharomyces cerevisiae resulted in the isolation of 1, which selectively inhibited a Hof1 deletion strain. Techniques including 1D and 2D NMR, HRESIMS, optical rotation, J-based analysis, and biosynthetic parallels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…These two structures, while diverse, do not overlap or even represent the breadth of scaffold variety that we have observed in studies of marine-derived fungi. Furthermore, in more recent explorations, we have focused on strains cultivated from deep water sediments, and found that intriguing, bioactive compounds are often encountered 18-20. The account below outlines our comprehensive evaluation of diketopiperazine-containing compounds produced by deep water sediment-derived fungi whose isolation was facilitated by T .…”
Section: Introductionmentioning
confidence: 99%
“…These two structures, while diverse, do not overlap or even represent the breadth of scaffold variety that we have observed in studies of marine-derived fungi. Furthermore, in more recent explorations, we have focused on strains cultivated from deep water sediments, and found that intriguing, bioactive compounds are often encountered 18-20. The account below outlines our comprehensive evaluation of diketopiperazine-containing compounds produced by deep water sediment-derived fungi whose isolation was facilitated by T .…”
Section: Introductionmentioning
confidence: 99%
“…Two phenylethanols ( 48 , 49 ) from terrestrial fungi, two aliphatic acids ( 50 , 51 ) isolated from mangrove fungi, and one polyketide synthase nonribosomal peptide synthetase ( 52 ) (Fig. ) isolated from terrestrial fungal samples were evaluated in our screening but failed to show plasmodial inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…The methyl proton H-24 at δ 2.00 exhibited a long-range coupling to sp 2 quaternary carbons C-2 (δ 172.5) and C-3 (δ 107.9), and carbonyl carbon C-4 (δ 195.6), suggesting the presence of an α, β-unsaturated carbonyl moiety. The long-range couplings from NH-7, H-9 and OH-9 to C-5, as well as the longrange couplings from H-9 to C-4 established the 1-oxa-7-azaspiro [4, 4] non-2-ene-4, 6-dione skeleton (Boot et al, 2007), similar to pseurotin A (Bloch and Tamm, 1981). The long-range couplings from H-9 to C-17 and from H-24 to C-14 established the total structure of 1.…”
Section: Biological Assaysmentioning
confidence: 96%